Paul Ricoeur - Simms, Karl (Routledge critical thinkers., 2003)
Paul Ricoeur is one of the most wide-ranging thinkers to emerge in the twentieth century. He has developed a unique 'theory of reading' or hermeneutics, which extends far beyond the reading of literary works to build into a theory for the reading of 'life'. For this reason, his work has impacted not only upon literary studies, but upon such disciplines as philosophy, psychoanalysis, history, religion, legal studies and politics. This introductory guide: * details Ricoeur's most significant contributions to contemporary critical thought * provides an intellectual context to his key ideas * explores the debate around his work on good and evil, psychoanalysis, metaphor, narrative, politics and justice * suggests the continuing relevance of Ricoeur's thought and examines the increasing interest in his work across a range of disciplines. Karl Simms also provides a guide to further reading, which offers advice on Ricoeur's publications and relevant secondary texts. Refreshingly clear and impressively comprehensive, Paul Ricoeur is the essential guide to an essential theorist.